Root caries incidence and increment in the population – A systematic review, meta-analysis and meta-regression of longitudinal studies. (October 2018) - Hariyani, Ninuk; Setyowati, Dini; Spencer, A. John; Luzzi, Liana; Do, Loc Giang
Abstract: Objectives: Previous meta-analyses of root caries incidence and increment studies reported different estimates due to the limited number of studies, heterogeneity and variations in studies included. Currently, new publications and approaches to handle heterogeneity are available. This research aims to systematically review and meta-analyse root caries incidence and increment, and use meta-regression to analyse heterogeneity. Sources: PUBMED and EMBASE databases were searched systematically. Study selection: Longitudinal studies on root caries incidence and increment, published in English language prior to 2017, were independently checked by two authors. A pooled incidence and increment of decayed/filled root surfaces (DFS) was estimated and meta-regression analysis was performed by length of follow-up (<2 years; 2years; 3–4years and ≥5years) and study type (observational population-based and clinical trial). Data: Of 737 articles, 20 were included for meta-analysis. The annualised root caries incidence and increment were 18.25%[CI = 13.22%–23.28%] and 0.45[CI = 0.37–0.53] root DFS respectively. Length of follow-up influenced the estimates, but not the study type. The annual root DFS incidence and increment from studies <2years were 32.95%[CI = 29.13%–36.77%] and 0.64[CI = 0.38–0.89] root surfaces respectively. Studies with 5+years follow-up, the annualised root caries incidence and increment were 9.4%[CI = 3.32%–15.48%] and 0.43[CI = 0.21–0.64] root surfaces respectively. Conclusions: Length of follow-up influenced root caries estimates due to a bias towards relatively healthier older adults retained in the study. Root caries increased over time even among the healthier older adults. Clinical significance: The increase in root caries, even among the healthier older adults, should be considered by both clinicians and healthcare planners/policy makers in their provision of services.